STUDYING THE EFFECT OF ANALYZING THE RELATIONSHIP BETWEEN SOME MONETARY VARIABLES AND REALITY ON THE IRAQI BALANCE OF PAYMENTS - Anwar Mezher Hamdullah; Zahrah Khlaif Rafak (American Journals, 2024)
The research aims to know the impact of the most important factors affecting the Iraqi balance of payments (1991-2017 AD) in order to reach a standard model for the relationship between variables and know their importance and the extent of their impact on the balance of payments. In order to achieve this goal, the study sought to test hypotheses that have a moral effect and a linear relationship between Both GDP, nominal exchange rate and real exchange rate in Iraq. The independent variables included in the model are more likely to explain the scale model than the independent variables not included. The most important of the results reached is that the values of the balance of payments in Iraq can be represented by a linear equation with the values of the gross domestic product and the values of the exchange rate, and that these variables together have a significant impact on the balance of payments, and that their interpretation rate is high, as they carry a significant percentage that explains 95% of the value. Balance of payments, while 5% could be due to random, unmeasurable factors such as the turbulent security and political situation.
Keywords: Balance of Payments - Real exchange rate - Gross Domestic Product.